Fish β-parvalbumin acquires allergenic properties by amyloid assembly - Martínez, Javier; Sánchez, Rosa; Castellanos, Milagros; Fernández-Escamilla, A. M.; Vázquez-Cortés, S.; Fernández-Rivas, M.; Gasset, M. (Swiss Medical Weekly, 2015)
PRINCIPLES: Amyloids are highly cross-β-sheet-rich aggregated states that confer protease resistance, membrane activity and multivalence properties to proteins, all essential features for the undesired preservation of food proteins transiting the gastrointestinal tract and causing type I allergy. METHODS: Amyloid propensity of β-parvalbumin, the major fish allergen, was theoretically analysed and assayed under gastrointestinal-relevant conditions using the binding of thioflavin T, the formation of sodium dodecyl sulphate- (SDS-) resistant aggregates, circular dichroism spectroscopy and atomic force microscopy fibril imaging. Impact of amyloid aggregates on allergenicity was assessed with dot blot. RESULTS: Sequences of β-parvalbumin from species with commercial value contain several adhesive hexapeptides capable of driving amyloid formation. Using Atlantic cod β-parvalbumin (rGad m 1) displaying high IgE cross-reactivity, we found that formation of amyloid fibres under simulated gastrointestinal conditions accounts for the resistance to acid and neutral proteases, for the presence of membrane active species under gastrointestinal relevant conditions and for the IgE-recognition in the sera of allergic patients. Incorporation of the anti-amyloid compound epigallocatechin gallate prevents rGad m 1 fibrillation, facilitates its protease digestion and impairs its recognition by IgE. CONCLUSIONS: the formation of amyloid by rGad m 1 explains its degradation resistance, its facilitated passage across the intestinal epithelial barrier and its epitope architecture as allergen. Peer Reviewed